Cellular and Molecular Mechanisms of Spinal Cord Vascularization - Vieira, Jose Ricardo; Shah, Bhavin; Ruiz de Almodovar, Carmen (Frontiers in Physiology, 2020)
During embryonic central nervous system (CNS) development, the neural and the vascular systems communicate with each other in order to give rise to a fully functional and mature CNS. The initial avascular CNS becomes vascularized by blood vessel sprouting from different vascular plexus in a highly stereotypical and controlled manner. This process is similar across different regions of the CNS. In particular for the developing spinal cord (SC), blood vessel ingression occurs from a perineural vascular plexus during embryonic development. In this review, we provide an updated and comprehensive description of the cellular and molecular mechanisms behind this stereotypical and controlled patterning of blood vessels in the developing embryonic SC, identified using different animal models. We discuss how signals derived from neural progenitors and differentiated neurons guide the SC growing vasculature. Lastly, we provide a perspective of how the molecular mechanisms identified during development could be used to better understand pathological situations.